Study of Kenmotsu manifolds with semi-symmetric metric connection - Sudhakar Chaubey; Sunil Kr Yadav (Universal Journal of Mathematics and Applications, 2018)
The present paper deals with the study of Kenmotsu manifolds equipped with a semi-symmetric metric connection. The properties of $η-$parallel Ricci tensor, globally symmetric and $φ-$symmetric Kenmotsu manifolds with the semi-symmetric metric connection are evaluated. In the end, we construct an example of a $3-$dimensional Kenmotsu manifold admitting semi-symmetric metric connection and verify our some results.